Evaluation of collagen in dermal wounds of rabbits treated with different sources of platelet-rich plasma - Ferraciolli, E.; Laposy, C. B.; Nogueira, M. R.; Justulin Junior, L. A. [UNESP]; Camargo Filho, J. C. [UNESP]; Horeira, V; Marques, M. E.; Nai, G.; Ozaki, G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
In order to compare the tissue regeneration of dermal wounds in treated and untreated rabbits serially with different sources of platelet rich plasma (PRP) gel, dermal biopsies were made in the dorsal region with the aid of an 8mm punch. The right side was treated with 0.9% NaCl and, on the left side, the different sources of PRPs (autologous, heterologous and homologous) on days 0, 3, 7, 10, 14 were applied and monitored for 17 days. At the end of the 17th day, histopathological evaluation of the wounds was performed. From the total of 24 animals, six rabbits (3 males and 3 females) were used only as donors to obtain the homologous PRP gel. A healthy, adult dog was used as a donor during the experiment to prepare the PRP gel from the heterologous group. The mean values of the fibers of the autologous and homologous groups were very similar (75.0 +/- 13.7 and 73.1 +/- 10.2, respectively), when compared to the means obtained in the control group (71.5 +/- 10.8). The collagen fibers of the heterologous group were inferior (P < 0.05) to the other groups (59.4 +/- 11.3). It is concluded that the heterologous source produces less organized and homogeneous collagen fibers and should be the last resource to be used in order to promote good quality healing.
Keywords: rabbits; dermal wound scaring; collagen fibers; platelet-rich plasma